2006
DOI: 10.1097/01.sla.0000234655.83517.56
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Errors Contributing to Trauma Mortality

Abstract: Preventable deaths will occur even in mature trauma systems. This review has identified error patterns that are likely common in all trauma systems, and for which policy interventions can be effectively targeted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
239
2
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(258 citation statements)
references
References 29 publications
10
239
2
7
Order By: Relevance
“…Gruen ve ark. (3) hastaneye ulaştırıl-mış 2594 politravma hastasında mortaliteye katkıda bulunan hata modellerini saptamaya çalışmışlar, hava yolu güvenliğinin sağlanamaması veya korunamamasının mortaliteye ilişkin en yaygın faktör olduğunu bulmuşlardır.…”
Section: Introductionunclassified
“…Gruen ve ark. (3) hastaneye ulaştırıl-mış 2594 politravma hastasında mortaliteye katkıda bulunan hata modellerini saptamaya çalışmışlar, hava yolu güvenliğinin sağlanamaması veya korunamamasının mortaliteye ilişkin en yaygın faktör olduğunu bulmuşlardır.…”
Section: Introductionunclassified
“…8 The authors reported that delayed intervention for ongoing intrathoracic hemorrhage most often delays the diagnosis of massive hemothorax with inadequate evacuation of blood from chest, or inadequate recognition of the volume that had already been evacuated. 8 The main treatment for life-threatening hemorrhagic shock following blunt thoracic trauma is the rapid control of bleeding. Our findings suggest that thoracotomy should not be excluded solely because of chest tube output that is lower than the traditional criteria.…”
Section: Roc Curves Of 1-h Chest Tube Output For Predicting Thoracotomymentioning
confidence: 99%
“…7 In a study performed at the Harborview Medical Center, patterns of errors contributing to inpatient trauma deaths in a 9-year period were identified. 8 Delayed intervention for ongoing intrathoracic hemorrhage contributed to 9.4% of recognized errors leading to death. 8 The authors reported that delayed intervention for ongoing intrathoracic hemorrhage most often delays the diagnosis of massive hemothorax with inadequate evacuation of blood from chest, or inadequate recognition of the volume that had already been evacuated.…”
Section: Roc Curves Of 1-h Chest Tube Output For Predicting Thoracotomymentioning
confidence: 99%
See 1 more Smart Citation
“…The services of protocolbased care, best practices guidelines, ATLS, massive blood transfusion services, advances in haemostasis, investigations, damage control surgeries, and specialist trauma services are all directed at saving patients in this category. [29][30][31] Late trauma deaths, representing the third peak, typically occur days to weeks after initial injury in those that survived the initial insult. This study found 30% of the trauma deaths belong to this category, which is in contrast to 20% described in the original study.…”
Section: Timing Of Deathmentioning
confidence: 99%